2019
DOI: 10.1051/e3sconf/20199002001
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Water Treatment Techniques on Cocopeat Media Filled Grow Bed Aquaponics System

Abstract: Aquaponics system is an innovative idea which combined both aquaculture and hydroponics systems. In this study performance of four different types of water treatment technique was investigated in cocopeat media filled grow bed aquaponics system. The techniques that had been investigated were mechanical filter, biological filter, combination of both mechanical and biological filters and grow media (cocopeat) itself as filtration media. The effectiveness these techniques were assessed through (i) water quality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This condition followed the study results of Kamauddin et al (2019) who stated that the use of cocopeat as a physical filter was insufficient to be utilized for water treatment in aquaponic system. The capability of water spinach as a good biological filter for catfish in aquaponic system was strengthened by the study results of Zahidah et al (2018) and Nazlia and Zulfiadi (2018).…”
Section: Discussionmentioning
confidence: 76%
“…This condition followed the study results of Kamauddin et al (2019) who stated that the use of cocopeat as a physical filter was insufficient to be utilized for water treatment in aquaponic system. The capability of water spinach as a good biological filter for catfish in aquaponic system was strengthened by the study results of Zahidah et al (2018) and Nazlia and Zulfiadi (2018).…”
Section: Discussionmentioning
confidence: 76%
“…Hitherto, in practice, three cultivation techniques in aquaponics systems are used: Nutrient film technique (Castillo-Castellanos et al, 2016), Media bed technique (Kamauddin et al, 2019), and Deep water culture technique (Somerville et al, 2014). The nutrient film technique ( Figure 5) is a hydroponic method that uses horizontal pipes (Somerville et al, 2014).…”
Section: Basic Cultivation Techniques In Aquaponics Systemsmentioning
confidence: 99%
“…Cronin et al [102] used a new filtration method to provide mechanical filtration by changing the flow direction of water so that heavy solids could be precipitated at the bottom of a radial flow separator/settler (RFS). Kamauddin et al [103] designed experiments to compare and analyze different water treatment technologies. The results showed that the plant growth rate and yield of the aquaponics system with mechanical filtration were the highest, and there was adequate quality of water.…”
Section: A Physical Filtration Equipmentmentioning
confidence: 99%